Soil-transmitted helminth infection, loss of education and cognitive impairment in school-aged children: A systematic review and meta-analysis. - Noel Pabalan; Eloisa Singian; Lani Tabangay; Hamdi Jarjanazi; Michael J Boivin; Amara E Ezeamama (Public Library of Science (PLoS), 2018)
Evidence of an adverse influence of soil transmitted helminth (STH) infections on cognitive function and educational loss is equivocal. Prior meta-analyses have focused on randomized controlled trials only and have not sufficiently explored the potential for disparate influence of STH infection by cognitive domain. We re-examine the hypothesis that STH infection is associated with cognitive deficit and educational loss using data from all primary epidemiologic studies published between 1992 and 2016.Medline, Biosis and Web of Science were searched for original studies published in the English language. Cognitive function was defined in four domains (learning, memory, reaction time and innate intelligence) and educational loss in two domains (attendance and scholastic achievement). Pooled effect across studies were calculated as standardized mean differences (SMD) to compare cognitive and educational measures for STH infected/non-dewormed children versus STH uninfected /dewormed children using Review Manager 5.3. Sub-group analyses were implemented by study design, risk of bias (ROB) and co-prevalence of Schistosoma species infection. Influential studies were excluded in sensitivity analysis to examine stability of pooled estimates.We included 36 studies of 12,920 children. STH infected/non-dewormed children had small to moderate deficits in three domains-learning, memory and intelligence (SMD: -0.44 to -0.27, P<0.01-0.03) compared to STH-uninfected/dewormed children. There were no differences by infection/treatment status for reaction time, school attendance and scholastic achievement (SMD: -0.26 to -0.16, P = 0.06-0.19). Heterogeneity of the pooled effects in all six domains was high (P<0.01; I2 = 66-99%). Application of outlier treatment reduced heterogeneity in learning domain (P = 0.12; I2 = 33%) and strengthened STH-related associations in all domains but intelligence (SMD: -0.20, P = 0.09). Results varied by study design and ROB. Among experimental intervention studies, there was no association between STH treatment and educational loss/performance in tests of memory, reaction time and innate intelligence (SMD: -0.27 to 0.17, P = 0.18-0.69). Infection-related deficits in learning persisted within design/ROB levels (SMD: -0.37 to -52, P<0.01) except for pre-vs post intervention design (n = 3 studies, SMD = -0.43, P = 0.47). Deficits in memory, reaction time and innate intelligence persisted within observational studies (SMD: -0.23 to -0.38, all P<0.01) and high ROB strata (SMD:-0.37 to -0.83, P = 0.07 to <0.01). Further, in Schistosoma infection co-prevalent settings, associations were generally stronger and statistically robust for STH-related deficits in learning, memory and reaction time tests(SMD:-0.36 to -0.55, P = 0.003-0.02). STH-related deficits in school attendance and scholastic achievement was noted in low (SMD:-0.57, P = 0.05) and high ROB strata respectively.We provide evidence of superior performance in five of six educational and cognitive domains assessed for STH uninfected/dewormed versus STH infected/not-dewormed school-aged children from helminth endemic regions. Cautious interpretation is warranted due to high ROB in some of the primary literature and high between study variability in most domains. Notwithstanding, this synthesis provides empirical support for a cognitive and educational benefit of deworming. The benefit of deworming will be enhanced by strategically employing, integrated interventions. Thus, multi-pronged inter-sectoral strategies that holistically address the environmental and structural roots of child cognitive impairment and educational loss in the developing world may be needed to fully realize the benefit of mass deworming programs.